2020
DOI: 10.1007/s41208-020-00263-3
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure and Spatial Patterns of Soft-Bottom Macrozoobenthos in Oualidia Lagoon, Moroccan Atlantic

Abstract: The paper analyse the composition, structure and spatial organization of the soft-bottom macrozoobenthos inhabiting Oualidia lagoon (Moroccan Atlantic coasts), as well as their relationships with the main environmental variables. Material for the study was collected from 43 stations in winter 2013. A total of 56 species belonging to 6 phyla were recorded and identified. Species diversity was highest in molluscs, crustaceans and polychaetes. We used a Hierarchical Ascending Classification and a non-Metric Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…Our results also showed the association of stations located in the subtidal with others in the intertidal areas in the identified clusters (G6, G7 and G8). In contrast to the results obtained in the Moulay Bousselham lagoon by [46] and in the Oualidia lagoon by [61], our assemblages do not show a clear dominance of one or two species.…”
Section: Spatial Patterns and Environmental Driverscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results also showed the association of stations located in the subtidal with others in the intertidal areas in the identified clusters (G6, G7 and G8). In contrast to the results obtained in the Moulay Bousselham lagoon by [46] and in the Oualidia lagoon by [61], our assemblages do not show a clear dominance of one or two species.…”
Section: Spatial Patterns and Environmental Driverscontrasting
confidence: 99%
“…Compared with previous studies, the number of species was higher than observed by [22]: 45, [23]: 54, [46]: 46 and lower than that obtained by [21]:173 taxa. In comparison with other lagoon systems, the species richness shows higher values than the lagoons of Sidi Moussa [55,57,58], Oualidia [59][60][61], Khnifiss [60,62], Ghar El-Melh [63], Mellah [64], Cabras [65,66], Celestun [67], Epe [68] and Lesina [69]. However, the species number was still lower than that Oualidia [54], Nador [70], Ria Formosa [71], Venice [72], Lagos [73], Bay of Muggia [74], Marano and Grado lagoon [75] and similar to those observed in Sacca di Goro lagoon [76].…”
Section: Benthic Macrofaunamentioning
confidence: 99%
“…In the connection area of marine and freshwater, generally, salinity level alteration is a vital environmental factor determining the benthic macroinvertebrate community structure and distribution (El Asri et al 2021;Zinchenko et al 2017). Boutoumit et al (2021) reveal that key factors determining the species composition and patterns of macrozoobenthos assemblages are the hydrographic regime (marine and terrestrial freshwater), sediment distribution and characteristics, and the sort of habitat (vegetated area).…”
Section: Correlation Between Ecosystem Characters Water Quality and T...mentioning
confidence: 99%
“…Historically, monitoring efforts in Oualidia lagoon have been focused on heavy metal pollution via the monitoring of sediment and marine molluscs (Zourarah et al, 2007;Maanan., 2008;Boutahar et al, 2019), hydrodynamics , faecal pollution (Escherichia coli and faecal streptococci), physico-chemical water parameters (Hennani et al, 2012;Hassou et al, 2014), and nutrient cycling (Damsiri et al, 2017). Research carried out on benthic macrofauna have been limited to the study of the polychaete assemblages (El Asri et al, 2018) and intertidal or subtidal species spatial distribution (Chaouti et al, 2019;El Asri et al, 2020), and no studies have attempted to use biotic indices for the assessment of the ecological status of the lagoon.…”
Section: Introductionmentioning
confidence: 99%